2017
DOI: 10.1515/acve-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Three Classic Forms of Natural Equine Glanders – A Disease With High Zoonotic Significance

Abstract: Equine glanders is a severe bacterial disease known since ancient times. Although eradicated in the most part of the world it is now considered re-emerging. Considering very scarce literature data, we used from formalin fi xed collection material: nasal septum, lung and skin specimens from naturally infected horses. Tissues were grossly examined and photographed. Tissue samples, after standard processing, were stained with HE, Congo red and Groccot and microscopically examined. Gross changes include nodules an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In this study, we have described the histopathological and immunohistochemical findings observed in 4 cases of naturally occurring equine glanders in Mongolia. Clinical, gross, and histological findings in the 4 glanderous horses are similar to those previously reported in chronic cases of equine glanders, 1,2,4,8 except for marked fibrin exudation surrounding the pyogranulomas and abscesses. Relatively active bacterial proliferation may correlate with increased vascular permeability and the resultant fibrin exudation and severe neutrophilic infiltration.…”
supporting
confidence: 84%
“…In this study, we have described the histopathological and immunohistochemical findings observed in 4 cases of naturally occurring equine glanders in Mongolia. Clinical, gross, and histological findings in the 4 glanderous horses are similar to those previously reported in chronic cases of equine glanders, 1,2,4,8 except for marked fibrin exudation surrounding the pyogranulomas and abscesses. Relatively active bacterial proliferation may correlate with increased vascular permeability and the resultant fibrin exudation and severe neutrophilic infiltration.…”
supporting
confidence: 84%